PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ANDROID PADA TOPIK SEL KELAS XI SMA - Kasturi, Annisa Majesty; Suryawati, Evi; Darmawati, Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to develop android-based interactive learning media that can be used as a means of student self-study during the pandemic. The research location is at the Laboratory of PMIPA FKIP Riau University and SMAN 1 Pekanbaru in May - August 2021. The development model used in this study is ADDIE which consists of analysis, design, and design stages. Data collection instruments in the form of validation sheets and response questionnaires. The validation results obtained an average value of 3.65 in the Very Valid category. The results of the Phase I Limited Trial and Phase II Trial obtained an average value of 3.90 and 3.80 in the Very Good category. This study shows that the developed android-based interactive learning media is valid and feasible to use as a source of student self-study and can be used during asynchronous learning processes on cell material.Key Words: Android, Cells, Multimedia Interactive learning.